A spatial analysis of subsidised bus route catchment feasibility in an urban area in Malaysia - Khor, Jia Min; Fatiah, A. A.; Ponrahono, Zakiah (Malaysian Institute of Planners, 2022)
This paper focuses on subsidized bus services provided by a local authority in Malaysia to determine the route's feasibility. This case study explores the catchment area of the designated bus stops in its route, the distance between the bus stops, the passengers' boarding, and alighting points, and the level of service. A Global Positioning System (GPS) device was used for an onboard survey to identify the boarding and alighting points, and the service catchment area was explored with the Geospatial Information System (GIS) tool. Findings indicate that the service level lacks sufficient facilities, proper accessibility, comprehensive information, and signage at bus stops. Furthermore, relatively poor performing bus service in passengers loading and timely arrival during peak periods. Next, an analysis of forty-one (41) catchment areas revealed that only 37% of the bus stops are within a catchment area. Recommendations for bus services include timely and accurate information to ease users to plan their journey and providing comfortable bus stops.